Insights into lateral marsh retreat mechanism through localized field measurements. Issue 2 (28th February 2016) - Bendoni, M.; Mel, R.; Solari, L.; Lanzoni, S.; Francalanci, S.; Oumeraci, H.
Abstract: Deterioration of salt marshes may be due to several factors related to increased anthropic pressure, sea level rise, and erosive processes. While salt marshes can reach equilibrium in the vertical direction, adapting to sea level rise, they are inherently unstable in the horizontal direction. Marsh boundaries are characterized by scarps with bare sediment below the vegetated surface layer that can be easily removed by wave‐induced erosion. In this work, we explore the different mechanisms involved in the erosion of marsh borders through the interpretation of field data. The analysis is based on a systematic field monitoring of a salt marsh in the Venice Lagoon subject to lateral erosion. Measurements included horizontal retreat of the scarp at various locations and wave height in front of the marsh during three storm surges. Continuous erosion and mass failures alternated during the observed period, leading to an average retreat up to 80 cm/yr. The data, collected roughly every month for 1.5 year, indicate that the linear relation that links the observed erosion rate to the impinging wave power exhibits a larger slope than that already estimated in literature on the basis of long‐term surveys. Moreover, an increase in the gradient of erodibility is detected along the marsh scarp, due to the combined action of soil strengthening by vegetation on the marsh surface and the impact of wave breaking at the bank toe, which promote cantilever failures and increase the lateral erosion rate. Key Points: Lateral erosion and wave height at a salt marsh from field measurements The toe of the bank is more erodible than the top, promoting mass failures A less erodible vegetated bank top may lead to relatively higher lateral retreat